Human security and climate change in Southeast Asia : managing risk and resilience - Elliott, Lorraine M.; Anthony, Mely Caballero (Abingdon, Oxon : Routledge, 2013)
'This book makes an important and timely contribution to debates about the relationship between climate change and security in Southeast Asia. It does so through a human security lens, drawing on local and regional expertise to discuss the threats that climate change poses to human security in Southeast Asia and to show how a human security approach draws attention to the importance of adaptation and strategies for social resilience. In doing so, it exposes the consequences of climate change, the impact on community rights and access, the special problem of border areas, before going on to investigate local and regional strategies for addressing the human security challenges of climate change'--Provided by publisher.
Human security, climate security and social resilience / Lorraine Elliott -- The economics of climate change in Southeast Asia / Juzhong Zhuang, Suphachol Suphachalasai and Jindra Nuella Samson -- Risk, vulnerability and resilience : climate change and the urban poor in Asia / Devanathan Parthasarathy -- Water regime resilience and community rights to resource access in the face of climate change / Keokam Kraisoraphong -- Reducing Emissions from Deforestation and Forest Degradation (REDD) : mitigation, adaptation and the resilience of local livelihoods / Enrique Ibarra Gene and Arif Aliadi -- The gender and climate debate : more of the same or new pathways of thinking and doing? / Bernadette P. Resurreccion -- Climate security and development in Southeast Asia : the limits of UNESCAP's green growth approach / Irene A. Kuntjoro -- Risk, resilience and human security in cross-border areas : the Greater Mekong Subregion, the heart of Borneo and the Coral Triangle / Fitrian Ardiansyah and Desak Putu Adhityani Putri -- ASEAN and climate change : building resilience through regional initiatives / Mely Caballero-Anthony -- Conclusion : conditions for enhancing human security / Lorraine Elliott.
Includes bibliographical references (p. [174]-199) and index.
Keywords: Climatic changes -- Social aspects -- Southeast Asia; Human security -- Environmental aspects -- Southeast Asia; Southeast Asia -- Environmental conditions -- Social aspects